Reconhecimento facial baseado em Gabor Wavelets com foveação - Santos, Thiago Oliveira dos (2006)
Due to the complexity and the high number of variables involved in the management activities, it is essential to the project manager to have some kind of automated support to perform her tasks. During the accomplishment of a software project, a high amount of knowledge is produced and used. Looking for the reuse of that knowledge in future projects, we need to provide means to retain and store the generated knowledge in a way to minimize the effort to obtain it in the future. In this context, knowledge management can be used to capture the knowledge and experience generated and accumulated during the software process and to promote the appearance of new knowledge. Experience constitutes a key factor in order to management activities can be accomplished with success. Thus, the benefits reached by the change of ideas during the accomplishment of those activities are evident. During this work, in order to support software project management using knowledge management in the software development environment ODE, we have developed and integrated to ODE an infrastructure to support software items characterization and search for similar items and an infrastructure to support group decision. To evaluate the potential of these infrastructures, we specialized them, respectively, to support project characterization and cooperative elaboration of risk plans.